2013
DOI: 10.1007/s00268-013-2226-z
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Evaluation of Missed Injuries in Trauma Patients, Before and After Formalising the Trauma Tertiary Survey

Abstract: ObjectiveThis study prospectively evaluated in-hospital and postdischarge missed injury rates in admitted trauma patients, before and after the formalisation of a trauma tertiary survey (TTS) procedure. MethodsProspective before-and-after cohort study. TTS were formalised in a single regional level II trauma hospital in November 2009. All multitrauma patients admitted between March–October 2009 (preformalisation of TTS) and December 2009–September 2010 (post-) were assessed for missed injury, classified into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 29 publications
1
33
1
2
Order By: Relevance
“…Even if the incidence of clinically significant missed injuries is unknown, they are more likely to lead to prolonged morbidity or mortality. Although mortality as a result of missed injuries is rare, a prospective study indicated that approximately 1% of the cohort required a surgical intervention for injuries detected after the hospital discharge 35 . Injuries are often neglected during the primary and secondary surveys in trauma patients; namely, studies have suggested that a formal tertiary survey protocol lowers the number of missed injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Even if the incidence of clinically significant missed injuries is unknown, they are more likely to lead to prolonged morbidity or mortality. Although mortality as a result of missed injuries is rare, a prospective study indicated that approximately 1% of the cohort required a surgical intervention for injuries detected after the hospital discharge 35 . Injuries are often neglected during the primary and secondary surveys in trauma patients; namely, studies have suggested that a formal tertiary survey protocol lowers the number of missed injuries.…”
Section: Discussionmentioning
confidence: 99%
“…The Australian Safety and Quality Goals for Health Care Consultation in February 2012 [8] reported that on average 2.5 errors occur nationwide during the treatment of severely injured patients. A study from Queensland, Australia published in 2014 estimated the average missed injury rate to be between 3.8 and 4.8% [9]. The low incidence in our study can be explained by the fact that RPH is a Level 1 Centre for adults in Western Australia with senior Trauma cover available till 11 PM on weekdays.…”
Section: Discussionmentioning
confidence: 76%
“…Kod dijafragmalnih I retroperitonealnih povreda i perforacija šupljih organa on je često lažno negativan. 12 Povrede dijafragme mogu biti asimptomatske a nalaz radiografije grudne duplje uredan. Zato je potrebno sprovesti rutinsku laparoskopiju kod svih pacijenata sa penetrantnom povredom leve ili prednje desne torakoabdominalne regije čak i u odsustvu simptoma.…”
Section: Greške U Zbrinjavanju Pacijenata Sa Povredama Grudnog Košaunclassified